12 Outcomes and modifiable resuscitative characteristics amongst pan-asian out-of-hospital cardiac arrest occuring at night – a multinational, prosepctive, observationel study. (21st May 2017) - Ong, M; Ho, AFW; Hao, Y; Pek, PP; Shahidah, N; Yap, S; Ng, YY; Kwanhatha, DW; Lee, EJ; Khruekarnchana, P; Wah, W; Liu, N; et al.
Abstract : Aim: Studies are divided on the effect of day-night temporal differences on clinical outcomes in out-of-hospital cardiac arrest (OHCA). This study aimed to elucidate the circadian variation in OHCA Methods: This was a prospective, observational study of OHCA cases across multinational Pan-Asian sites. We excluded traumatic cases, less than 18 year-old, cases where resuscitation was not attempted or started but terminated before arrival at Emergency Department, and missing time-of-call-received data. Cases were divided according to time call received by dispatch centres into day (0700 H-1900H) and night (1900 H-0659H). Primary outcome was 30 day survival. Secondary outcomes were prehospital and hospital modifiable resuscitative characteristics. Results: 55881 cases qualified for analysis. 40.3% occurred at night. Incidence was lower at night (p<0.001), with a trough at 0300 hour. There was a large increase from 0700 H-0900H. After adjusting for potential confounders, odds of 30 day survival at night was lower with an adjusted odds ratio of 0.79 (95% Confidence Interval, 0.73–0.86, p<0.001). Overall, night cases have lower 30 day survival with a trough at midnight. However this diminished when considering only unwitnessed cases. On univariate logistic regression, occurrence at night was associated with decreased provision of bystander CPR, bystander AED application and prehospital adrenaline. Conclusion: In this international cohort, 30 day survival was worse in OHCA occurring at night. There were circadian patterns in incidence. Circadian patterns in 30 day survival diminished when considering only unwitnessed cases. Bystander CPR and bystander AED application were significantly lower at night. This would at least partially explain the decreased survival at night. Conflict of interest: None declared. Funding: None declared.